Pengaruh Pemberian Agen Hayati Pada Benih Dan Pupuk Bokashi Terhadap Mutu Fisiologis Benih Kedelai (Glycine max L. (Merill) Kultivar Grobogan - Eka Siti Windia; Sumadi Sumadi; Anne Nuraini (Agrologia, 2018)
Physiological quality of seeds could be seen from viability and vigor. The used of matriconditioning treatment using biological agent and bokashi fertilizer could be the way to enhance physiological quality of seeds. The objective of experiment was to determind the most effective dosage interaction of biological agent and bokashi fertilizer to improve physiological quality of seeds.This research was held at Ciparanje Experimental Farm and Laboratory of Seed Technology Faculty Agriculture Universitas Padjadjaran.from November 2016 until February 2017.  The experiment’s method design using randomized block design factorial pattern with Duncan’s Multiple Range Test (DMRT) at 5 %. The Cultivar that used for this research was Grobogan with Bokashi that tested at 0 ton/ha, 16 ton/ha, 32 ton/ha, and 48 ton/ha respectively combined with matriconditioning that used biological agent and control without biological agent. The biological agent that used for this treatment were Trichoderma spp., Azotobacter spp., Trichoderma spp + Azotobacter spp., with three replication.  The result of the experiment showed that interaction of biological agent and bokashi fertilizer affected the weight of 100 seeds and vigor index. The treatment that used Trichoderma spp. + Azotobacter spp. and bokashi fertilizer 48 ton/ha has showed that this dosage was the best for weight of 100 seeds parameter. Thus the treatment with trichoderma and azotobacter without bokashi fertilizer showed that this treatment affected the best for vigor index.Keyword: Soybean seeds, physiological quality, Trichoderma spp., Azotobacter spp., Bokashi.